2016
DOI: 10.1016/j.anl.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymph node metastasis in adenoid cystic carcinoma of oral cavity and oropharynx: A collective international review

Abstract: The purpose of this study was to establish general guidelines in the management of the N0 neck of oral cavity and oropharyngeal adenoid cystic carcinoma (AdCC) in order to improve the survival of these patients and/or reduce the risk of neck recurrences. The incidence of cervical node metastasis at diagnosis of head and neck AdCC is variable, and ranges between 3% and 16%. Metastasis to the cervical lymph nodes of intraoral and oropharyngeal AdCC varies from 2% to 43%, with the lower rates pertaining to palata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 43 publications
3
11
2
3
Order By: Relevance
“…None of the oropharyngeal ACC was positive for p16 and/or high risk human papillomavirus. In our cohort, it appeared that intraoral/oropharyngeal ACCs were associated with higher risk (38%) of regional metastasis compared to those from other sites (14%), which was in agreement with results from previous studies (16, 32). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…None of the oropharyngeal ACC was positive for p16 and/or high risk human papillomavirus. In our cohort, it appeared that intraoral/oropharyngeal ACCs were associated with higher risk (38%) of regional metastasis compared to those from other sites (14%), which was in agreement with results from previous studies (16, 32). …”
Section: Discussionsupporting
confidence: 93%
“…In the study herein, lymph node metastasis was found in a significant number of patients, being 15% in the entire cohort and 25% in patients who had lymph node sampling; this seems to be higher than the reported lymph metastasis rate in typical adenoid cystic carcinoma (1, 15, 16, 28, 32), and is likely to be related to selection bias in performing lymph node sampling and referral bias as the study cohort included patients from a tertiary cancer center. Among the 21 patients who harbored nodal metastasis, the majority (13/21, 62%) were patients with intraoral or oropharyngeal ACC.…”
Section: Discussioncontrasting
confidence: 65%
“…Adenoid cystic carcinoma with high-grade transformation is another subgroup of ACC although it is very rare. The striking clinical features of ACC-HGT was the high propensity for lymph node metastasis present, which was in 3 of the 5 cases and with shortened survival 38 . Investigations of the molecular alterations underlying this extremely aggressive behavior are minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed with ACC were reviewed from the archives of the Ninth People's Hospital affiliated to Shanghai Jiao Tong University during 2000-2019. A total of 36 high-grade ACC patients with available follow-up records were selected for this study, and the corresponding para n-embedded ACC specimens were obtained from the Department of Oral Pathology, the Ninth People's Hospital, following the approval of the University Institutional Ethics Committee according to histologic criteria 38,41 . All patients signed the informed consent.…”
Section: Cases and Tissuesmentioning
confidence: 99%
“…Powerful local invasion, migration, and hematogenous metastasis lead to the difficulty in clinic treatment and prognosis. Therefore, the effects of various biological factors on the aggressive potentials of SACC and the molecular mechanism of SACC pathogenesis have been extensively studied . However, these processes are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%